PHYTOCHEMICAL CHARACTERISATION AND ANTI-MICROBIAL ACTIVITY OF VITEX NEGUNDU LEAVES - Verma, S. M. (Medknow Publications & Media Pvt Ltd, 2001)
Fresh leaves of vitex negundu were collected and macroscopic and microscopic characters were determined. Soxhlet extraction of the powdered leavers was carried out using petroleum ether (40:60) and chloroform. Idenitification of important phytoconstituents was carried out. Characterization by TLC showed the presence of vitexin. The processed leaf extract was tested for antimicrobial activity. The results indicated antibacterial activity of the extract.